Variation in the promoter of the sorbitol dehydrogenase gene MdSDH2 affects binding of the transcription factor MdABI3 and alters fructose content in apple fruit. (14th December 2021) - Wang, Zhengyang; Ma, Baiquan; Yang, Nanxiang; Jin, Ling; Wang, Lan; Ma, Songya; Ruan, Yong‐Ling; Ma, Fengwang; Li, Mingjun
SUMMARY: Fructose (Fru) content is a key determinant of fruit sweetness and quality. An F1 hybrid population of the apple cultivars 'Honeycrisp' × 'Qinguan' was used to investigate the quantitative trait locus (QTL) regions and genes controlling Fru content in fruit. A stable QTL on linkage group (LG) 01 in 'Honeycrisp' was detected on the single nucleotide polymorphism (SNP) genetic linkage maps. In this region, a sorbitol dehydrogenase (SDH) gene, MdSDH2, was detected and showed promoter variations and differential expression patterns between 'Honeycrisp' and 'Qinguan' fruits as well as their hybrids. A SNP variant (A/G) in the MdSDH2 promoter region (SDH2p‐491) affected the binding ability of the transcription factor MdABI3, which can affect the expression of MdSDH2 . Promoter sequences with an A nucleotide at SDH2p‐491 had stronger binding affinity for MdABI3 than those with a G. Among 27 domesticated apple cultivars and wild relatives, this SNP (A/G) was associated with Fru content. Our results indicate that MdSDH2 can alter Fru content as the major regulatory gene and that ABA signaling might be involved in Fru content accumulation in apple fruit. Significance Statement: Here, we detected a stable overlapping QTL region of fructose content in apple fruit with a SNP genetic map, and confirmed that A/G SNP variation in the promoter of the sorbitol dehydrogenase gene MdSDH2 in this QTL region affects binding of the transcription factor MdABl3, which regulates MdSDH2 expression and fructose accumulation. Our results demonstrate the major role of the candidate gene MdSDH2 in regulating fructose content of apple fruit.